Optimization of Chicken Farm Renovation Project Using PERT, CPM technique and POM-QM software - Abdul Halim, Muhammad Haziq Faris; Siti Noor Asyikin Mohd Razali (Enhanced Knowledge in Sciences and Technology, 2024)
Construction is an important sector in every country to ensure the development of the nation. There are several problems in this sector; the most common is the delay of projects and a short budget. This study focuses on construction data obtained from the Selangor Veterinary Department, specifically the renovation of a large-scale modern chicken coop project involving numerous workers and commercial machinery. Like any project, it encounters challenges related to time and cost constraints. The study employs the Program Evaluation and Review Technique (PERT) to delineate the project network, integrates the Critical Path Method (CPM) to identify critical paths, and applies project crashing with linear programming to optimise activity duration reduction and minimise costs. The utilisation of PERT yields an illustrative network diagram conducive to comprehensive analysis. The CPM computation determines a project completion time of 72 days, with a noteworthy 98.87% probability of achieving completion within 88 days. Each phase is individually analysed to enhance flexibility, and the CPM and PERT results indicate a completion time of 51 days for Phase 1 with a 98.80% probability and 19 days for Phase 2 with a 97.26% probability of completion within 28 days. Additionally, project crashes are implemented to further expedite the project. Based on the project crash results, a reduction of 17 days is feasible at an additional cost of RM 2081.50. Consequently, the project was successfully completed in 55 days at a cost of RM 16538.50. This study makes a big contribution to the construction sector in this country. At the same time, this study opens a new perspective on phased construction in project management.